Connectomic analysis of unilateral dual-lead thalamic deep brain stimulation for treatment of multiple sclerosis tremor. Issue 2 (15th March 2022) - Wong, Joshua K.; Patel, Bhavana; Middlebrooks, Erik H.; Hilliard, Justin D.; Foote, Kelly D.; Okun, Michael S.; Almeida, Leonardo
Abstract: Tremor is a common symptom in multiple sclerosis and can present as a severe postural and action tremor, leading to significant disability. Owing to the diffuse and progressive nature of the disease, it has been challenging to characterize the pathophysiology underlying multiple sclerosis tremor. Deep brain stimulation of the ventralis intermedius and the ventralis oralis posterior thalamic nuclei has been used to treat medically refractory multiple sclerosis tremors with variable results. The aim of this study was to characterize multiple sclerosis tremor at the network level by applying modern connectomic techniques to data from a previously completed single-centre, randomized, single-blind prospective trial of 12 subjects who were treated with unilateral dual-lead (ventralis intermedius + ventralis oralis posterior) thalamic deep brain stimulation. Preoperative T1 -weighted MRI and postoperative head CTs were used, along with applied programming settings, to estimate the volume of tissue activated for each patient. The volumes of tissue activated were then used to make voxel-wise and structural connectivity correlations with clinically observed tremor suppression. The volume of the tissue-activated analyses identified the optimal region of stimulation at the ventralis oralis posterior ventralis intermedius border intersecting with the dentato-rubro-thalamic tract. A regression model showed strong connectivity to the supplemental motor area was positively associated with tremor suppression ( r  = 0.66) in this cohort, whereas connectivity to the primary motor cortex was negatively associated with tremor suppression ( r  = −0.69), a finding opposite to that seen in ventralis intermedius deep brain stimulation for essential tremor. Comparing the structural connectivity to that of an essential tremor cohort revealed a distinct network that lies anterior to the essential tremor network. Overall, the volumes of tissue activated and connectivity observations converge to suggest that optimal suppression of multiple sclerosis tremor will likely be achieved by directing stimulation more anteriorly toward the ventralis oralis posterior and that a wide field of stimulation synergistically modulating the ventralis oralis posterior and ventralis intermedius nuclei may be more effective than traditional ventralis intermedius deep brain stimulation at suppressing the severe tremors commonly seen in complex tremor syndromes such as multiple sclerosis tremor. Abstract : Wong et al . report that supplemental motor area connectivity was positively associated with tremor suppression, whereas primary motor cortex connectivity was negatively associated with tremor suppression in unilateral dual-lead thalamic deep brain stimulation for multiple sclerosis tremor. Optimal tremor involved neuromodulation of the ventralis oralis thalamic nucleus. Graphical Abstract: Graphical Abstract